Advocacy-Based Consumer Protection for Online Game Account Sabotage Victims: A Positive Law and Maqashid Sharia Perspective - Wahyu; Supriyadi, Aditya Prastian; Fakhruddin; Miftahul Huda (Faculty of Law, University of Merdeka Malang, 2025)
The proliferation of digital commerce in Indonesia has generated new forms of consumer vulnerability, most notably the deliberate sabotage of online game accounts following completed transactions a phenomenon that inflicts both material and psychological harm upon consumers yet remains institutionally unaddressed. This study examines advocacy-based consumer protection for victims of online game account sabotage in Malang City, analyzed through the dual normative lenses of positive law and Maqashid Sharia. Employing an empirical legal research design with a socio-legal approach, the study draws on in-depth interviews with the Consumer Protection Technical Implementation Unit (UPT) of Malang City and five victim-informants, supplemented by normative analysis of applicable statutory instruments. The findings reveal that while Law Number 8 of 1999 concerning Consumer Protection and Law Number 1 of 2024 concerning Electronic Information and Transactions provide a sufficient normative basis for institutional advocacy, the UPT has not operationalized this mandate in digital consumer disputes. From the Maqashid Sharia perspective, account sabotage constitutes a simultaneous violation of hifz al-mal, hifz al-nafs, and hifz al-'aql, rendering institutional advocacy a legal and moral imperative. This study proposes a five-stage advocacy model and recommends the establishment of a dedicated digital consumer division within the UPT, supported by targeted regulatory reform governing virtual digital asset transactions.